Influence of the uniaxial stress p2 and transverse fields E1 and E3 on the phase transitions and thermodynamic characteristics of GPI ferroelectric materials - Левицький, Р. Р.; Зачек, І. Р.; Вдович, А. С.; Біленька, О. Б.; Levitskii, R. R.; Zachek, I. R.; Vdovych, A. S.; Bilenka, O. B. (Видавництво Львівської політехніки, 2021)
Для дослідження ефектів, що виникають під дією одновісного тиску p2 і електричних полів E1 та E3, використано модифіковану модель GPI шляхом врахування п’єзоелектричного зв’язку структурних елементів, які впорядковуються, з деформаціями εj . В наближенні двочастинкового кластера розраховано вектори поляризації та компоненти тензора статичної діелектричної проникності механічно затиснутого кристала, їх п’єзоелектричні та теплові характеристики. Досліджено одночасну дію тиску p2 і полів E1 та E3 на фазовий перехід та фізичні характеристики кристала.

A modified GPI model that accounts for the piezoelectric coupling between the ordered structural elements and the strains εj has been used for studing of effects arising in GPI ferroelectrics under the action of the uniaxial stress p2 and electric fields E1 and E3. The polarization vectors and components of static dielectric permittivity are calcucated in the two-particle cluster approximation for mechanically clamped crystal, and piezoelectric and thermal parameters are also determined. The influence of the simultaneous action of the stress p2 and fields E1 and E3 on the phase transition and physical characteristics of GPI crystal has been studied.
Вплив одновісного тиску p2 та поперечних полів E1 і E3 на фазові переходи та термодинамічні характеристики сегнетоактивних матеріалів GPI
Keywords: сегнетоелектрики; фазовий перехід; діелектрична проникність; п’єзомодулі; зсувна напруга; ferroelectrics; phase transition; dielectric permittivity; piezoelectric modules; shear stress